Institutional Reforms in the Context of the Future of Europe Conference From the Perspective of a Central-Eastern European Country: Hungary - Sándor, Lénárd (Maastricht 30: A Central European Perspective, 2025)
The history of the institutionalised cooperation in Europe now looks back to more than seven decades. The rapid development of the European integration has had its formidable successes including, particularly, the ability to contribute to preserving the peace in the old continent after the cataclysm of the Second World War or to create an internal market along with the fundamental freedoms Europeans enjoy today. On the other hand, the European cooperation has also had its shortcomings and failuresespecially in the past one and a half decades and has arrived at a crossroad from many aspects. The Treaty of Maastricht was a symbolic stage in this history, and the question of renewal is more urgent than ever. This paper therefore sheds light on the importance of the Maastricht Treaty in this historical development of the European integration. In light of this, it seeks to answer the question of why different regions have different viewpoints vis-à-vis the future of the European integration and it aims to explore the main Central-European or Hungarian perspective. Keywords: History of the European integration, Maastricht Treaty, Treaty of Lisbon, European democracy, European Court, Transnational list, lead candidate system